2022
DOI: 10.48550/arxiv.2205.01646
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Implementation of an efficient, portable and platform-agnostic cryptocurrency mining algorithm for Internet of Things devices

Abstract: Recently, there has been a remarkable amount of research being done in both, the fields of Blockchain and Internet of Things (IoT). Blockchain technology synergises well with IoT, solving key problems such as privacy, concerns with interoperability and security. However, the consensus mechanisms that allows trustless parties to maintain an agreement, the same algorithms that underpins cryptocurrency mining, are usually extremely computationally expensive, making implementation on low-power IoT devices difficul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Another consensus algorithm, proof of burning (PoB), relies on the ability to bind tokens to a specific address; the greater the number of tokens bound is, the greater the probability of obtaining billing rights is. The problem with this algorithm is that it is not conducive to the circulation of tokens, that is, all users tend to bind a certain number of tokens to a specific address instead of using them for transactions [48]. There is also a PoSP consensus algorithm, which mainly depends on the storage capacity of users.…”
Section: Competency-based Proof Algorithmmentioning
confidence: 99%
“…Another consensus algorithm, proof of burning (PoB), relies on the ability to bind tokens to a specific address; the greater the number of tokens bound is, the greater the probability of obtaining billing rights is. The problem with this algorithm is that it is not conducive to the circulation of tokens, that is, all users tend to bind a certain number of tokens to a specific address instead of using them for transactions [48]. There is also a PoSP consensus algorithm, which mainly depends on the storage capacity of users.…”
Section: Competency-based Proof Algorithmmentioning
confidence: 99%
“…Noyen et al (2014) provided an in-depth analysis of the process of data exchange using Bitcoin and how sensing-as-a-service can benefit from it. Dua (2022) reported that a newly developed algorithm could mine cryptocurrencies, such as Bitcoin, on low-power IoT equipment without connecting them to an external device, and Delgado-Segura et al…”
Section: Literature Reviewmentioning
confidence: 99%